VLS-like growth and characterizations of dense ZnO nanorods grown by e-beam process - Agarwal, Dinesh C.; Chauhan, R. S.; Avasthi, D. K.; Sulania, I.; Kabiraj, D.; Thakur, P.; Chae, K. H.; Chawla, Amit; Chandra, Ramesh; Ogale, S. B.; Pellegrini, G.; Mazzoldi, P. (Journal of Physics D-Applied Physics, 2009)
We present a new approach to produce ZnO nanorods in a reproducible manner at a temperature lower than other physical vapour deposition techniques, such as the vapour-liquid-solid mechanism. Arrays of well-aligned ZnO nanorods of uniform diameter have been synthesized on the Si substrate precoated with Au, using a simple electron beam evaporation method without the flow of any carrier gas. Scanning electron microscopy and atomic force microscopy characterizations show that as-grown nanorods are well aligned and uniform in diameter. X-ray diffraction measurements and clear lattice fringes in high-resolution transmission electron microscopy image show the growth of good quality polycrystalline hexagonal ZnO nanorods and a < 0 0 2 > growth direction. The polarization-dependent studies of near edge x-ray absorption fine structure (NEXAFS) are performed to investigate the electronic structure of the zinc and oxygen ions. The analysis of NEXAFS spectra at different angles of incidence of photon flux indicates the formation of ZnO nanorods having anisotropic behaviour of O and Zn states. The photoluminescence spectrum exhibits strong ultraviolet emission at 385 nm and the UV-visible spectrum also shows a band-gap transition around 390 nm indicating the good quality of nanorods. The catalytic growth mechanism of the ZnO nanorods is discussed on the basis of experimental results in this work.

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal

Highly efficient chemoselective N-tert butoxycarbonylation of aliphatic/aromatic/heterocyclic amines using diphenylglycoluril as organocatalyst - Awasthi, Amardeep; Mukherjee, Anagh; Singh, Mandeep; Rathee, Garima; Vanka, Kumar; Chandra, Ramesh (Tetrahedron, 2020)
An efficient approach for the Chemoselective N-tert-butoxycarbonylation of a variety of amines using diphenylglycoluril as organocatalyst has been described. For the first time, a plausible mechanism for the N-tert-butoxycarbonylation has been proposed using density functional theory (DFT) calculations supported by NMR studies. The reusability of the organocatalyst and observation of the desired N-Boc protected amines being formed without the formation of side products like urea, oxazolidinone, isocyanate, and N, N-di-Boc derivatives makes the present protocol desirable. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: DFT studies; Diphenylglycouril; N-tert butoxycarbonylation; organocatalyst; Proton shuttle mechanism